Preventive bacterial translocation and control of Ventilator-Associated Pneumonia: A qualitative study - Yulis Setiya Dewi; Arina Qona'ah; Hidayat Arifin; Rifky Pradipta; Lizy Sonia Benjamin (JKP (Jurnal Keperawatan Padjajaran), 2022)
Background: Bacterial translocation is one cause of ventilator-associated pneumonia among patients treated in the Intensive Care Unit. The study aimed to observe critical nurses information about bacterial translocation prevention and ventilator-associated control in clinical settings.